Memahami Penderitaan Ayub Di Masa Pandemi Covid-19: Tafsir Ayub 42:7-17 - Rori, Hana (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2022)
The Covid-19 pandemic crisis in various areas of life cannot be denied. Various ways by the government and community organization to remain resistant continue to be implemented. This paper aims to interpret the book of Job 4:7-17 using the method of narrative criticism. Explore the meaning in it and integrate it during a pandemic. The result found is that recovery is a part of life after experiencing suffering. The attitude of helping each other during a pandemic is needed for recovery-restoration, like the story of Job who was helped by the surrounding environment. Recovery cannot be separated from acceptance as well as release. Accepting the understanding that suffering is not only a bad part of life but has an overall positive impact on life. This study also discusses the importance of respecting nature as part of God's creation, so that nature does not fight back, because nature and humans are equal according to God's wisdom. This study suggests further research, especially the study of reader responses regarding the story of Job during the pandemic.AbstrakKrisis pandemi Covid-19 terhadap berbagai bidang kehidupan tidak dapat disangkal. Berbagai cara pemerintah maupun organisasi masyarakat untuk tetap resistan terus dilaksanakan. Tulisan ini bertujuan untuk menafsir kitab Ayub 4:7-17 menggunakan metode kritik naratif. Menggali makna di dalamnya serta memadukannya di masa pandemi. Hasil yang ditemui adalah pemulihan merupakan bagian kehidupan setelah mengalami penderitaan. Sikap saling tolong menolong di masa pandemi diperlukan untuk pemulihan seperti kisah Ayub yang dibantu oleh lingkungan sekitarnya. Pemulihan tidak lepas dari penerimaan juga pelepasan. Menerima pemahaman derita bukan hanya bagian buruk kehidupan tapi memberikan dampak positif secara keseluruhan di dalam kehidupan. Penelitian ini juga membahas pentingnya menghargai alam sebagai bagian ciptaan Tuhan, agar alam tidak melawan balik, karena alam dan manusia setara menurut hikmat Tuhan. Penelitian ini menyarankan penelitian lanjutan khususnya kajian respon pembaca mengenai kisah Ayub di masa pandemi.